2022
DOI: 10.21203/rs.3.rs-1774503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of antibody-specific deglycosylation and immune evasion by Streptococcal IgG-specific endoglycosidases

Abstract: Bacterial pathogens have evolved diverse and intricate mechanisms to evade the human immune system, including the production of immunomodulatory enzymes. Streptococcus pyogenes secretes two multi-modular endo-β-N-acetylglucosaminidases, EndoS and EndoS2, that specifically deglycosylate the conserved N-linked glycan at Asn297 on IgG Fc, disabling antibody-mediated effector functions. Amongst thousands of known carbohydrate-active enzymes, EndoS and EndoS2 represent just a handful of enzymes that are specific to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
(103 reference statements)
1
4
0
1
Order By: Relevance
“…6c). In addition, we obtained a native stable complex between BT1285i and Fc HM at low protein concentration (0.05 mg mL -1 ) that we visualized by negative-stain transmission electron microscopy (NS-TEM), which did not require chemical crosslinking to be stabilized as previously reported for the EndoS-Fc complex 57 , due to the high affinity of BT1285 for HM glycans on Fc. By NS-TEM analysis of the BT1285i:Fc-HM complex we generated a three-lobed ~19 Å structure, in which one molecule of BT1285 is positioned to attack the Asn297-linked glycan on each Fc protomer and making contact just with the HM N-glycan on N297, which also supported the 2:1 BT1285i:Fc-HM stoichiometry (Fig.…”
Section: Conformational Accessibility Of N-glycans Affects Their Reco...mentioning
confidence: 83%
“…6c). In addition, we obtained a native stable complex between BT1285i and Fc HM at low protein concentration (0.05 mg mL -1 ) that we visualized by negative-stain transmission electron microscopy (NS-TEM), which did not require chemical crosslinking to be stabilized as previously reported for the EndoS-Fc complex 57 , due to the high affinity of BT1285 for HM glycans on Fc. By NS-TEM analysis of the BT1285i:Fc-HM complex we generated a three-lobed ~19 Å structure, in which one molecule of BT1285 is positioned to attack the Asn297-linked glycan on each Fc protomer and making contact just with the HM N-glycan on N297, which also supported the 2:1 BT1285i:Fc-HM stoichiometry (Fig.…”
Section: Conformational Accessibility Of N-glycans Affects Their Reco...mentioning
confidence: 83%
“…Rituximab, an anti-CD20 chimeric monoclonal antibody, targets B cells and is often used as a therapeutic for B cell lymphomas ( 37 ). After purification by protein A affinity chromatography ( 38 ) and treatment with the IgG-specific endoglycosidase EndoS2 ( 39 , 40 ) to remove heterogeneous glycosylation at residue Asn297, three potential products with unique masses that are easily detectable by liquid chromatography–mass spectrometry (LC-MS) can result from such a coexpression, including an intact Fc (~50 kDa), an intact IgG (~150 kDa), and a monovalent IgG molecule (Fab 1 Fc; ~100 kDa) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic studies of enzymes in complex with their glycan substrate have provided insight into the mechanism of action of endoglycosidases [11,12,[57][58][59]. Our recent structure of EndoS in complex with its IgG1 Fc substrate [55] and a cryo-electron microscopy study [56] provided further insight. Here, we present the crystal structure of EndoS2 in complex with IgG1 Fc substrate at a resolution of 3.0 Å (Table 1), with N-linked glycans modelled using the carbohydrate module in Coot [60] and validated using Privateer [61], as shown in Figure 1.…”
Section: Main Textmentioning
confidence: 86%
“…These endoglycosidases are multi-domain enzymes, with the catalytic glycosidase domain and the so-called carbohydrate binding module (CBM) being of particular interest [12,[52][53][54]. Recent structural studies revealed that the functional role of the CBM in EndoS is not to bind carbohydrate, but rather to specify peptide binding on the Fc surface [55,56], which provided a structural rationale for the abrogated enzymatic activity of EndoS lacking the CBM [52,53], further explaining the inability of EndoS to cleave glycans from denatured IgG [6]. Similarly, it is known for that the CBM of EndoS2 is essential for activity.…”
Section: Main Textmentioning
confidence: 99%